Accidental intra-arterial injection of enoxaparin sodium leading to abdominal wall expanding subcutaneous hematoma and abdominal wound: case report-vascular - Howell, Caroline; Simman, Richard (Frontiers in Surgery, 2025)
IntroductionEnoxaparin sodium (Lovenox®) is a commonly used anticoagulant medication that is self-administered via subcutaneous injection to prevent the formation of pathologic blood clots. It is used as a bridge to long-term anticoagulation with warfarin in patients at high risk for thromboembolic events. It is generally well-tolerated and has a favorable safety profile. The most common injection site reactions caused by enoxaparin sodium are urticaria, ecchymosis, and skin and fat necrosis.Case ReportA 56 year-old female with extensive thromboembolic history was completing an enoxaparin sodium bridge to warfarin when she accidentally self-injected enoxaparin sodium into the left superficial epigastric artery, resulting in the formation of a large expanding hematoma and the development of hemorrhagic shock. Controlling the bleeding required reversal of anticoagulation, transfusion, and coil embolization of the affected arteries. Surgical evacuation of the hematoma was performed, and the resultant wound was managed postoperatively with negative pressure wound therapy (NPWT) for one month. After discontinuation of NPWT, the wound was allowed to heal by secondary intention using dressing changes.ConclusionsThe findings of this case report suggest that NPWT followed by conventional dressings can be used to close and heal the wound created by surgical hematoma evacuation.